Perbedaan Pengaruh Dehidrasi 2.2 % Dan 2.8% Terhadap Prestasi Lari 400 Meter - Wati, Isti Dwi Puspita (Universitas Pendidikan Indonesia, 2021)
Dehydration is a case that will happen when exercising. The allowed dehydration level for a single exercise for health is still uncertain. Based on a review of research, dehydration up to 2% can lower mood but has not decreased aerobic performance. Information on the allowed level of dehydration to maintain exercise and performance still needs to be done. The research method used was an experimental pre-test post-test method. This study compared 2.2% and 2.8% dehydration levels on 400 meters running performance. The population of this study was all Sports Coaching Education students class of 2017 and 2018. The sample grouping was administered randomly into two groups. The first group was the 2.2% dehydration group consisted of 16 students. The second group was the 2.8% dehydration group consisted of 25 students. The dehydration process was conducted passively by doing sunbathing while using a raincoat. Bodyweight was measured before dehydration up to several times to reach the desired level of dehydration. The measurement of the 400-meter run was carried out before weight measurement and after dehydration. The data were analyzed by Mann-Whitney U test. The results of the data analysis concluded that there was no difference in the 400-meter run performance at the two levels of dehydration. Dehydration between 2.2% level and 2.8% level equally lowered the 400-meter running performance. This study suggests that the athlete's hydration level when exercising should be kept below 2.2% to achieve optimal performance. During training, athletes should be provided with drinks to maintain hydration levels.